Was 70 CE a watershed in Jewish history?: on Jews and Judaism before and after the destruction of the Second Temple - Schwartz, Daniel R.; Ṿais, Ze'ev; Clements, Ruth A. (Ancient Judaism and early Christianity, 2012)
Was 70 CE a watershed in Jewish history? : three stages of modern scholarship, and a renewed effort / Daniel R. Schwartz -- "Found written in the book of Moses" : priests in the era of Torah / Martha Himmelfarb -- The other side of Israelite priesthood : a sociological-anthropological perspective / Gideon Aran -- "A kingdom of priests" : did the Pharisees try to live like priests? / Hanan Birenboim -- Sectarianism before and after 70 CE / Jodi Magness -- Were priests communal leaders in late antique Palestine? : the archaeological evidence / Zeev Weiss -- Place beyond place : on artifacts, religious technologies and the mediation of sacred place / Ori Schwarz -- Priests and priesthood in Philo : could he have done without them? / Jutta Leonhardt-Balzer -- Sanctity and the attitude towards the Temple in Hellenistic Judaism / Noah Hacham -- Doing without the Temple : paradigms in Judaic literature of the diaspora / Michael Tuval